Restoration techniques for the heritage building / Kirkuk Qishla as a case study - Yunus, Sumbul Muhammed (Journal of Architecture and Urbanism, 2020)
National heritage buildings are considered as the memory of the cities and its civilization’s legacy. Such buildings are receiving more attention these days especially from architectures who are trying to restore them by using the proper techniques to bring them back to their former appearance to serve the community in the present time. From that point, the general goal of this research is to concentrate on the used techniques of restoring national heritage buildings by using the proper materials for the damaged or the collapsed parts as the restoration process differs from a building to another. All these points should be done according to the laws and protocols of UNSCO and ICOMOS to keep the authentic features of the building and pass it on to the next generations. This research deals specifically and practically with restoring the Qishla building in Kirkuk as a restoration sample. Some parts of that building collapsed recently and the research aims to save that building by studying the techniques of restoring it using the materials and building techniques of the era the building was built in. This research rises an important point, which is finding a general prospective of scientific and technical ways in restoring cultural heritage buildings which are made from stone specifically. From all that above the main issue that this research deals with is “The unclear techniques of restoring cultural heritage buildings in general and the restoration process of Qishla building with stone in specific”. Accomplishing the aim of this research lies in two points: First: Studying the rules which govern the restoration process of cultural heritage buildings. Second: Studying the restoration process of Qishla building and that includes; the restoration process with stone should be done by examining the chemical and physical features of the stone, durability of the used stone, conducting chemical tests in international labs as (ACMAE ANALYSES/ Canada) and the last step is to analyze and discuss the results to take final decisions.